A Reusable Eu3+ Complex for Naked‐Eye Discrimination of Methanol from Ethanol with a Ratiometric Fluorimetric Equilibrium in Methanol/Ethanol Mixtures. Issue 44 (20th November 2019) - Leal, João P.; Paz, Filipe A. Almeida; Mendes, Ricardo F.; Moreira, Tiago; Outis, Mani; Laia, César A. T.; Monteiro, Bernardo; Pereira, Cláudia C. L.
Abstract : Immediate naked eye distinction of methanol from ethanol can be performed by simple dissolution, in each of these solvents, of either [Na][EuFOD4 ] (1 ) complex or in mixture of products from the reaction between [P6, 6, 6, 14 ][Eu(FOD)4 ] and NaOPhMe3, referred as 2, ([P6, 6, 6, 14 ] + = trihexyltetradecylphosphonium cation, FOD – = 1, 1, 1, 2, 2, 3, 3‐heptafluoro‐7, 7‐dimethyloctane‐4, 6‐dionate). Additionally, an easy, low‐cost, efficient and fast spectrofluorimetric method for the detection and quantification of methanol in mixtures with ethanol is described. This method is based on the changes in the Eu 3+ luminescence in the visible region due to the interaction of the [P6, 6, 6, 14 ][Eu(FOD)4 ] complex with these alcohols. A limit of detection as low as 15 % (w/w) of methanol in mixtures of ethanol/methanol is discussed considering a linear calibration curve. Abstract : The reaction product between [P6, 6, 6, 14 ][Eu(FOD)4 ] and NaOPhMe3 forms an equilibrium in solution that allows for an easy, low‐cost, efficient and fast spectrofluorimetric method for the detection and quantification of methanol in mixtures with ethanol based on the changes in the Eu 3+ luminescence in the visible region.